Bilateral Fibular Graft: Biological Reconstruction after Resection of Primary Malignant Bone Tumors of the Lower Limb. (16th April 2013) - Niethard, Maya; Tiedke, Carmen; Andreou, Dimosthenis; Traub, Frank; Kuhnert, Mario; Werner, Mathias; Tunn, Per-Ulf
Abstract : This paper deals with bilateral vascularized fibular grafts (BVFG) as a method for reconstruction of metadiaphyseal defects of the femur and tibia in young patients suffering from malignant bone tumors of the lower limb. This reconstructional technique was used in 11 patients undergoing metadiaphyseal resection of lower limb malignant bone tumors. All patients with Ewing's sarcoma and osteosarcoma had multimodal treatment according to the EURO-E.W.I.N.G 99 or COSS-96 protocol. Median FU was 63 months. None of the patients experienced local recurrence during FU. 2 patients died due to distant disease during FU. Full weight- bearing was permitted after a mean of 8 months. The median MSTS score was 87%. Complications occurred in five patients. None of the complications led to failure of the biological reconstruction or to amputation. Biological reconstruction of osseous defects is always desirable when possible and aims at a permanent solution. Good functional and durable results can be obtained by using BVFG for the reconstruction of metadiaphyseal defects of the femur and tibia. Radiotherapy in the multimodal setting increases the risk for graft or fixation failure.